Retail Company Strategy Facing Industrial Revolution 4.0 - Salihah Khairawati (International Journal of Social Science and Business, 2020)
Facing changes in business environment, the companies should make adjustments in their operations. The role of information technology encourages everything in the internet (internet of things), which also has an impact on the retail industry. Retail companies improve themselves in facing changes in their industrial environment. The purpose of this article is to examine some retail businesses that have developed online shops in the current era and to formulate the retail company strategies to face the industrial revolution including redesigning business models and dynamic abilities, human resource readiness, developing features and shopping applications at retail shops and attractive promo offers for consumers. It is hoped that this study can provide input for retail shop managers in developing their business strategies